Personal financial management practices of selected UP students living away from home - Canlas, Zarina V. (College of Home Economics, University of the Philippines Diliman, 2015)
The study examined selected undergraduate students‟ overall personal financial management practices and social learning opportunities using a descriptive survey. Specifically, the study investigated budgeting, saving, spending, credit, and financial planning practices. It also identified the relationship of social learning opportunities such as discussing with and observing parents and friends and financial management practices. The effect of gender, bank account, ATM card, and credit card ownership to financial management practices were also sought out. The sample consists of 189 undergraduate students living on-campus, obtained through convenience sampling. Data were analyzed using descriptive statistics, Pearson‟s product-moment correlation coefficients, and t-tests. The results showed that respondents have satisfactory scores on all areas of personal financial management studied. Results also suggest that discussing and observing practices with parents and friends were found to be potent predictors of positive financial management practices. Higher scores for discussing with and observing practices of parents and friends meant better financial practices. On the other hand, gender and some financial characteristics were determined to have an effect on certain financial management practices. In particular, women practiced keeping a record of their expenses more than men. Meanwhile, ATM card owners set financial goals as compared with those who do not own ATM cards. Also, respondents who are credit card users buy on impulse and buy things often than those who do not use credit cards. Lastly, non-credit card users buy only the things needed compared with credit card users.